PENGARUH KUALITAS LAYANAN DAN KUALITAS PRODUK TERHADAP KEPUASAN NASABAH TABUNGAN ( Studi pada Bank BRI unit Randublatung 1 Blora) (Students' Journal of Economic and Management, 2013)
This study is a study that examined the effect of quality of service and product quality to customer satisfaction savings in Bank BRI Unit 1 Blora Randublatung . Objects in this study are customers of Bank BRI Unit 1 Blora Randublatung . In this study the samples taken are as many as 100 people in which the retrieval technique using purposive sampling and sampling based on the desires and characteristics that have been determined by researchers . The method of analysis used data validity test , reliability test , multiple linear regression , t-test, f and test the coefficient of determination . Regression results show that the quality of service and product quality has an effect on customer satisfaction savings . Where the variables a cool [ unyai biggest influence is the quality of the product . From the results of the study also showed that the quality of service and product quality either partially or simultaneously positive and significant effect on customer satisfaction savings . From the research findings , the managerial implications for the management of Bank BRI unit 1 is Randublatung Blora should seriously pay attention to the service in order to beat the competition and make new innovations to improve the quality of service both from the physical aspect , employee and resource management policies for added comfort .   Keywords : Quality of Service , Quality Products and Satisfaction